UPAYA LEGALITAS UMKM MELALUI PEMBUATAN NOMOR INDUK BERUSAHA (NIB) DAN SERTIFIKAT PRODUKSI PANGAN INDUSTRI RUMAH TANGGA (SPP-IRT) DI DESA SUELA, KECAMATAN SUELA, KABUPATEN LOMBOK TIMUR - Tantowi, M. Rizal; Iqbal, Muhammad; Rizky , Mochammad; Kurniawan, Ivan; Mahabbati, Lathifatul; Fazadilla, Afizha Nurul; Suwari, Ni Made Mita Ari; Mulianti, Ema; Yuliyati, Yuliyati; Yeyen, Yeyen (Jurnal Wicara, 2023)
University of Mataram Real Work Lecture on Village Community Empowerment (KKN-PMD) with the theme "Preneur Village" which was held for 54 days in Suela Village, Suela District, West Lombok Regency which started from 12 June 2023 to 12 August 2023 aiming to help MSMEs in obtaining business licenses, namely Business Identification Number (NIB) and Home. Industry Food Production Certificate (SPP-IRT). Most of the MSMEs in Suela Village do not have legal business licenses, as it is known that MSMEs themselves play a very important role for the economy of Suela Village. The increasing participation of the community in the MSME field has led to an increase in the number of MSME actors in Suela Village. However, with the lack of knowledge about business legality and licensing, many MSMEs do not have business licenses such as Business Identification Numbers (NIB) and Home Industry Food Production Certificates (SPP-IRT). The method used to overcome these problems is to carry out observations and surveys as well as data collection on MSMEs in each hamlet, register business licenses, and carry out outreach to the community. University of Mataram KKN-PMD students assist rural MSMEs in issuing their business permits through Online Single Submission (OSS) and provide understanding related to the importance of legality in doing business and product marketing through socialization held by KKN-PMD University of Mataram students for the continued development of MSMEs in the Village Suela.